Negócio social: uma alternativa para as transformações sociais no mercado direcionado à população de baixa renda - Silva, Alexandre Viegas da (Universidade do Vale do Rio dos Sinos, 2016)
Facing the social problems that the low-income segment have faced, there is great concern in the search for social and market solutions that can help to minimize the effects of the social deficit caused in the population at the base of the economic pyramid. In this context, the social business got notoriety in the academic, organizational and media scenery to take position itself as a new alternative that contributes to the promotion of social transformation addressed to the low-income population, promoting social and economic inclusion. This happens through the products and services offered by the social business to this audience that aim to solve social problems, taking into account the individual and collective impact. This study tried to understand how the social business helps to promote social changings in the market targeted to low-income population. Therefore, it takes as a theoretical base as social business approaches and social transformations and field research addresses one single case study made at Banco Bem, in Vitória (ES). Therefore, a qualitative research was developed, organized into two distinct phases: the first tried to identify the different types of inclusion, in addition to the social business approach traditionally features and identify the facilitating and inhibiting factors that interfere with the promotion of social changings. This first phase was developed through semi-structured interviews with 15 different actors involved in the social business studied as the manager, and their beneficiaries. Later, the data were analyzed from the content analysis. The second phase focuses with the life path, which analyzes the individual experience of three people in the community who were benefited by the Banco Bem and had their lives impacted by this business. The main results, the study shows the identification of new types of inclusion that can generate a social business, as well as social and economic, and the identification of other factors that facilitate and makes the promotion of social changings difficult. The trajectory of life as reporting of social changings signaled that the individual and economic reality of the people interviewed has been modified from the moment they were benefited by the actions of the Banco Bem in the community. The statements highlighted the benefits and changings in their lives and the community. All of them highlighted the community's social context issues, demonstrating a differentiated looking at the acquired benefits. The social changings promoted by the Banco Bem in low-income community are associated with results as for instance , valuing people, the reduction of social vulnerability, new social and economic reality, community empowerment, integration and community engagement and new opportunities social and economic choices for local human development.
Keywords: Negócios sociais; Transformações sociais; Inclusão social e econômica; População de baixa renda; Impacto social; Social business; Social transformations; Social and economic inclusion; Population of low income; Social impact; ACCNPQ::Ciências Sociais Aplicadas::Administração